The evolution and influencing factors of trade-embodied CO2 emissions transfer from China’s provinces to ASEAN countries - Chen, Jie; Wu, Sanmang; Li, Qiuping (Frontiers in Climate, 2025)
This study systematically examines the evolution and driving factors of embodied CO2 emission transfers in trade between Chinese provinces and ASEAN countries from 2002 to 2017. Employing a global multi-regional input–output (MRIO) model embedded with Chinese provincial data and structural decomposition analysis (SDA), we quantify the CO2 emissions embodied in exports (EEE) from 30 Chinese provinces to 10 ASEAN member countries. The analysis explores temporal trends, provincial and sectoral distribution, export routes, and driving forces. The key findings are as follows: (1) As China-ASEAN economic ties have strengthened, China’s EEE to ASEAN have shown a sustained upward trend, with Indonesia, Malaysia, Thailand, and Vietnam being the primary recipients. Heavy industries such as electricity, metal smelting, non-metallic mineral products, and chemicals are the dominant sources of these embodied emissions. (2) Coastal provinces such as Guangdong, Jiangsu, and Zhejiang have consistently served as major contributors to EEE. However, the contribution from several inland provinces has increased in later periods, revealing a spatial pattern of “coastal dominance and inland indirect participation” in interprovincial carbon transfer. (3) The export routes have shifted from predominantly international circulation toward a coexistence of domestic and international dual circulation, indicating the growing resilience of China’s domestic market and supply chains under the “dual circulation” strategy. (4) The expansion of final demand in ASEAN countries is identified as the primary driver behind China’s increasing EEE, whereas reductions in carbon intensity and structural upgrading of exports have partially offset the growth in emissions. This study highlights the importance of holistically considering inter-provincial disparities in emission transfers and advocates for improving regional and sectoral coordination in carbon mitigation policies, aiming to facilitate a green transition in China–ASEAN trade relations.